2013
DOI: 10.3324/haematol.2013.093724
|View full text |Cite
|
Sign up to set email alerts
|

Patient- versus physician-reporting of symptoms and health status in chronic myeloid leukemia

Abstract: © F e r r a t a S t o r t i F o u n d a t i o ning of health status and symptom severity, for a set of core symptoms related to first-line imatinib therapy, between patients and their treating physicians. Secondary objectives were to investigate whether patient-reported or physicianreported symptoms better reflect patients' overall health status, and to identify factors that may predict discrepancies between patients' versus physicians' ratings of symptom severity. Methods Study population and proceduresWe app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 29 publications
6
61
0
1
Order By: Relevance
“…19 Also, a recent CML study has shown that physicians tend to under-estimate symptom severity and over-estimate the overall health status of their patients. 20 This evidence underscores the need for directly asking patients themselves about their disease and treatment burden, and also confirms, with empirical data, the previously raised concerns about the current practice of assessing intolerance to TKIs (i.e. not patient-reported).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 72%
See 1 more Smart Citation
“…19 Also, a recent CML study has shown that physicians tend to under-estimate symptom severity and over-estimate the overall health status of their patients. 20 This evidence underscores the need for directly asking patients themselves about their disease and treatment burden, and also confirms, with empirical data, the previously raised concerns about the current practice of assessing intolerance to TKIs (i.e. not patient-reported).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 72%
“…20 This evidence underscores the need for directly asking patients themselves about their disease and treatment burden, and also confirms, with empirical data, the previously raised concerns about the current practice of assessing intolerance to TKIs (i.e. not patient-reported).…”
supporting
confidence: 72%
“…Следует отметить, что в последнее время в между-народном гематологическом сообществе при оценке эффекта и безопасности лечения ХМЛ все большее внимание уделяется оценкам самих пациентов [15][16][17][18][19][20], которые содержат информацию о заболевании и лечении, полученную непосредственно от больного и позволяющую судить об эффекте проводимого ле-чения, а также о его рисках с точки зрения самого па-циента. Таким образом, при комплексной оценке эф-фекта и безопасности терапии ХМЛ, помимо определения клинического эффекта и побочных ре-акций, важными составляющими являются качество жизни и профиль симптомов больного [15, [21][22][23][24][25].…”
Section: контакты: татьяна ивановна ионова Tation16@gmailcom в статьunclassified
“…The impact of comorbidities was studied during imatinib treatment in the German CML IV study which enrolled patients between 16 and 88 years old (median, 53 years). 6,7,35 In a recent report, 1519 of these patients were analyzed by cohorts according to their Charlson Comorbidity Index (CCI) at diagnosis. 35 Higher CCI was significantly associated with lower OS.…”
Section: Side Effectsmentioning
confidence: 99%
“…6,7,35 In a recent report, 1519 of these patients were analyzed by cohorts according to their Charlson Comorbidity Index (CCI) at diagnosis. 35 Higher CCI was significantly associated with lower OS. At 8 years, the probabilities for OS for CCI 2, 3-4, 5-6, and .7 were approximately 94%, 89%, 78%, and 46%.…”
Section: Side Effectsmentioning
confidence: 99%